AJAGTURA: STRATEGI AGROFORESTRI UNTUK PENINGKATAN PENDAPATAN DAN KESEJAHTERAAN PETANI YANG MELESTARIKAN LINGKUNGAN LAHAN KERING - Alfarizi, Mohamad; Haeruni; Wartisah, Wiwin; Darmawan, Rizki; Agib Al-Ansori, Irwan; Arnito, Melsi; Adawiyah, Rabiatul; Sulistia Ningsih, Dina; Sukma Tirani, Laras; Tejo Wulan, Sri (Jurnal Wicara, 2025)
The Real Work Lecture (KKN) is an intracurricular activity aimed at empowering communities through various service activities, such as counseling and training. In 2024, the KKN PMD program of Mataram University was conducted in Akar-Akar Village, North Lombok Regency, focusing on improving community livelihoods through dryland management. The village has significant agricultural potential but faces various challenges, including reliance on monoculture corn farming, limited understanding of sustainable land management, and restricted access to agricultural technology. The goal of this KKN program is to address these issues through counseling and the implementation of agroforestry systems. The activity methods included obtaining permits, problem identification, community counseling, and the development of agroforestry systems in demonstration plots. The results showed that the counseling successfully increased community understanding of crop diversification and the benefits of agroforestry. The implementation of agroforestry by planting high-value crops such as crystal guava and longan proved effective in enhancing land productivity and maintaining environmental sustainability. In conclusion, this KKN program successfully provided initial solutions to improve farmers' welfare and agricultural sustainability in Akar-Akar Village.